Unravelling causes of poor crop response to applied N and P fertilizers on African soils. (8th February 2022) - Sileshi, Gudeta W.; Kihara, Job; Tamene, Lulseged; Vanlauwe, Bernard; Phiri, Elijah; Jama, Bashir
Summary: A number of studies across sub-Saharan Africa have recently reported poor crop responses and low agronomic use efficiencies of applied nitrogen (AEN), phosphorus (AEP) and potassium (AEK). However, the conditions under which non-responsiveness occurs, its underlying causes and its probability of occurrence on different soil types are not well understood. Using data from 542 sites and 14 soil types in 23 African countries, we provide novel insights into the linkage between lack of response to applied N, P and K, the mineralogy of soils and their resilience to erosion. We estimated mean responses as well as the probabilities (ϕ) of no response in terms of response ratio (RR), yield gain (YG) and agronomic efficiency. Here we defined 'no response' as zero agronomic response to fertilizer inputs in a given site and year indexed by either RR ≤ 1, AEN ≤ 0, AEP ≤ 0 or AEK ≤ 0. The highest risks of no response were recorded on the iron-rich Plinthosols (ϕ = 0.26) followed by the aluminium-rich Alisols (ϕ = 0.16) and the erosion-prone Lixisols (ϕ = 0.16) and Leptosols (ϕ = 0.13). In terms of yield gains, the highest risk of low response (i.e., YG ≤ 0.5) was recorded on Alisols (ϕ = 0.47) and the lowest on Fluvisols (ϕ = 0.05). Cambisols, Fluvisols, Luvisols and Nitisols were deemed highly responsive to NPK fertilizer. The risks of no response were significantly higher on soils derived from siliceous than mafic parent materials, soil types with low resilience to erosion, soils with low-activity clays and high P fixation capacity. It is concluded that maize grain yields can exceed 3 t ha-1 with high probability (ϕ > 0.80) on Andosols, Nitisols and Vertisols, but with very low probability (ϕ < 0.30) on Alisols and Arenosols. It is also concluded that across soil types and agroecological zones, the risk of no response is up to two times more on farmers' fields than on research stations. Here, we discuss the implications of these finding for the design and location of future agronomic trials. We also provide insights to guide the targeting of fertilizer subsidies where nutrients can be more efficiently used.